Inequality and top incomes - Charlotte Bartels; Daniel Waldenström (Global Labor Organization (GLO), 2021)
This chapter comprises three main parts. The first part is about data sources, the definitions of income, and the methodologies used to estimate top income shares. Both the standard sources and methods used by the traditional top income studies are described. Further, new developments that employ new sources and estimation approaches are added, a detailed survey of the top-correction methods for surveys including reweighting and replacing top incomes is provided and approaches to align surveys, income tax data, and national accounts are contrasted. The second part of the chapter is a description of the main trends of top income shares that are the result of the previous studies. Different measures discussed in the methods section are presented and compared. The third part of the chapter surveys the literature on the determinants of top income shares. The focus of the third part is on studies that propose new methods to establish links between driving factors and top income shares.
Keywords: D31; N3; 330; Income inequality; top incomes